1991
DOI: 10.1111/j.1545-5300.1991.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Documenting a Time‐Bound, Circular View of Hierarchies: A Microanalysis of Parent‐Infant Dyadic Interaction

Abstract: This article presents a new theory that separates the levels of communication and relates them circularly, namely, by separating time from space/meaning variables. Documenting this proposition requires sequential microdescriptions--a far-out project in the field of family therapy. In an extensive study of clinical and nonclinical families, starting with available microanalytic data on nonverbal parent-infant dialogue, distinct time organizations have been found to modify the degree of circularity between the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…For instance, Kaye and Fogel (1980) demonstrated that the mother's gaze orientations towards her baby frame the infant's gaze orientations towards her: the mother's gaze is oriented toward the infant in a more stable way than the reverse. Fivaz-Depeursinge (1991) showed that the parent's holding of the infant in vis-" a a-vis and at dialogue distance is a necessary condition for gaze interaction and in turn a necessary condition for expressive interactions. Finally, Frascarolo et al (1997) showed that the body configuration drawn by three partners, parents and infant, and corresponding to an equilateral triangle including all partners, is a necessary condition for gaze interaction in three-way interactions.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kaye and Fogel (1980) demonstrated that the mother's gaze orientations towards her baby frame the infant's gaze orientations towards her: the mother's gaze is oriented toward the infant in a more stable way than the reverse. Fivaz-Depeursinge (1991) showed that the parent's holding of the infant in vis-" a a-vis and at dialogue distance is a necessary condition for gaze interaction and in turn a necessary condition for expressive interactions. Finally, Frascarolo et al (1997) showed that the body configuration drawn by three partners, parents and infant, and corresponding to an equilateral triangle including all partners, is a necessary condition for gaze interaction in three-way interactions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Lausanne family model, the directions of influences are reciprocal, but asymmetrical: The parents exercise a stronger influence by framing the development of the child whereas the child exercises a weaker influence, only indicating the effect of their framing. The fact that the parents' influence on the interactions is stronger and that their rate of change is less important than the child's may explain the stability of the family alliance ͑Fivaz- Depeursinge, 1991;Fivaz-Depeursinge, Fivaz, & Kaufmann, 1982͒. In exploring the establishment of these alliances, it is perhaps helpful to trace how these alliances are formed during the transition to parenthood. Pregnancy is not only a period of development of the embryo in the mother's womb but also is a period of psychological preparation of the parents for parenthood and for their relationship with their child.…”
mentioning
confidence: 97%
“…Fivaz-Depeursinge, Corboz-Warnery, and collaborators (Fivaz-Depeursinge, 1991;Corboz-Warnery et al, 1993) have developed a setting for the study of mother -infant interactions and fatherinfant interactions in a joint (mother -father -infant) play situation, the Lausanne Triadic Play (extensively described below). In this setting, dyadic, as well as triadic parent -infant interactions, can be observed and analyzed.…”
mentioning
confidence: 99%